The use of aminoglycoside antibiotic therapy in neutropaenic patients with haematological disease - Zent, Clive Steven; Zent, Clive Steven (Department of Medicine, 2017)
The use of aminoglycosides in the treatment of the febrile neutropaenic patient with haematological disease is difficult and often suboptimal. This study reviews the available literature to establish therapeutic guidelines in this population and then reports the use of a Bayesian statistics based predictive model to implement and manage therapy in 10 patients. A review of the literature on aminoglycoside Pharmacology and clinical use is essential to determine therapeutic guidelines for this population. Aminoglycosides are amino sugars in glycosidic linkage and are polycations at physiological PH. The antibiotic effect is mediated through inhibition of protein synthesis and disruption of cell membrane integrity. Principal use is in treatment of Gram negative infection although aminoglycosides have activity against some Gram positive organisms including staphylococci. Aminoglycosides are inactive against anaerobes. Acquired resistance is mediated by bacterial enzymatic drug metabolism. Aminoglycosides are nephro- and ototoxic, this is the major constraint in clinical use.